Investigation of Soil Infiltration Rate at Universiti Tun Hussein Onn Malaysia - Piriyadaarshini Ravindran; Zarina Md Ali; Noor Aliza Ahmad (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
Urbanization challenges the natural water cycle, leading to increased runoff surface and elevated risks of rainstorms and floods at UTHM. This study evaluates soil infiltration rates at two selected locations within the University Tun Hussein Onn Malaysia (UTHM). The purpose of this study is to determine the type and gradation of soil and to understand how soil type and vegetation cover influence soil infiltration rates and capacities under varying weather conditions. The study employs the double-ring method to measure and analyze infiltration rates, subsequently generating an infiltration rate curve under different land cover surfaces. The findings revealed that the grass-covered Musolla area had much higher infiltration rates and overall permeability than the bare terrain near the Tunku Tun Aminah Library. On day 1 (a sunny day), the library area had a high initial infiltration rate that gradually decreased, whereas Musolla maintained a consistently high infiltration rate. On day 2 (light rain), the library area experienced a rapid fall in infiltration rate as the soil approached saturation, whereas Musolla maintained a consistent rate supported by grass coverage. On Day 3 (heavy rain), the library area became completely saturated, with almost no infiltration, indicating a high risk of runoff and erosion. In contrast, Musolla maintained strong absorption despite alternating rainy and dry weather. The results highlight the crucial role of vegetation in enhancing soil permeability and managing water, underscoring the importance of grass cover in mitigating soil compaction and improving urban water absorption. The anticipated results will be to support UTHM's commitment to sustainable development and facilitate stormwater management strategies, thereby addressing the challenges posed by urbanization and enhancing the campus's resilience against potential water-related hazards.